2002
DOI: 10.3354/meps234171
|View full text |Cite
|
Sign up to set email alerts
|

Feeding mechanisms in the gastropod Crepidula fecunda

Abstract: The gastropod Crepidula fecunda feeds in 2 distinct ways: grazing of the substrate and suspension feeding. The taenioglossan radula plays a role in both processes. In the former, the radula rasps the surface, and the material is immediately ingested. This means of food acquisition is mainly used by motile individuals, i.e. juveniles and adult males. Adult females are sessile, and are only able to rasp the area beneath the head region, severely limiting the amount of food acquired. Females brooding egg capsules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 17 publications
5
42
1
Order By: Relevance
“…Slower particle velocity could be the result of reduced ciliary beat frequency on the gills of intertidal C. peruviana, something that could be examined in a future study. Overall, the particle transport velocities found in this study were slower than those previously found in C. peruviana (~1,400 µm s −1 , Chaparro et al 2002). However, our experiments were performed at cooler temperatures than in Chaparro et al (2002), and C. peruviana in our study were first removed from their substrates and transferred to plastic plates, both of which may have contributed to the slower particle velocities that we found.…”
Section: Resultscontrasting
confidence: 55%
See 1 more Smart Citation
“…Slower particle velocity could be the result of reduced ciliary beat frequency on the gills of intertidal C. peruviana, something that could be examined in a future study. Overall, the particle transport velocities found in this study were slower than those previously found in C. peruviana (~1,400 µm s −1 , Chaparro et al 2002). However, our experiments were performed at cooler temperatures than in Chaparro et al (2002), and C. peruviana in our study were first removed from their substrates and transferred to plastic plates, both of which may have contributed to the slower particle velocities that we found.…”
Section: Resultscontrasting
confidence: 55%
“…The tip of the endoscope was inserted through the hole in the plastic substrate and into the pallial cavity of the organism until the gill could be visualized. Filming was initiated once snails began filtering, and then, a suspension of nontoxic bright orange particles (2-10 µm diameter, Chaparro et al 2001bChaparro et al , 2002 was added to the water near the incurrent feeding stream. These particles are easy to visualize, and they move along the gill at the same speed as does I. galbana (Mardones et al 2013).…”
Section: Particle Transport Velocity On the Gillmentioning
confidence: 99%
“…The effects of C. fornicata filtration on primary production in the water column are probably moderate because the chlorophyll biomass has remained constant, despite the proliferation of this invasive species during the past 10 years (Del Amo et al 1997). By contrast, C. fornicata probably has a major influence on microorganisms at the water-sediment interface and may change species composition and dynamics in overlying water and in the sediments by selecting the particles according to size and quality (Chaparro et al 2002). As reported for other suspension feeders (Lavrentyev et al 1995;Lavrentyev and Yang 2000), C. fornicata may remove a large proportion of protozoans and phytoplankton compared with bacteria, which affect the microbial food web and associated carbon and nitrogen cycling processes by increasing bacterial abundances and activities.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, considering its respiration, C. fornicata can consume a significant part of the pelagic carbon production of the bay and can divert carbon and nitrogen primary production from planktonic to benthic food webs. However, the genus Crepidula exhibits dual feeding modes of suspension feeding and grazing of the substrate (Chaparro et al 2002). Suspended particles are not the only food source for C. fornicata, especially for motile individuals (i.e., small individuals, juveniles, and adult males) that graze the biofilm on top of the substrate.…”
Section: Discussionmentioning
confidence: 99%
“…The polychaete Boccardia pugettensis was reported to regulate the balance of time spent between deposit and suspension feeding as a response to changes in food condition (Taghon & Greene 1992). The gastropod Crepidula fecunda showed both suspension feeding and grazing strategies during its incubation periods (Chaparro et al 2002). The facultative deposit feeder M. balthica feeds on deposited materials at low water (Brafield & Newell 1961), when they occur at high density (Marinelli & Williams 2003), and also during their juvenile stage (Rossi et al 2004).…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%